Car-Following Model-Based Stochastic Distance Regulation Between Vehicles⁎. Issue 31 (2018) - Li, Jingwei; Zhao, Changli; Yue, Hongwei; Fu, Wenjun
Abstract: The problem of car-following model-based stochastic distance regulation between vehicles with consideration of the disturbance caused by the sensitivity of the driver is researched in this paper. An stochastic distance regulator is designed based on the car-following dynamic model, for the purpose of distance regulation between vehicles. The validation of the proposed stochastic regulator is given by the numerical simulation. The simulation results show that the distance between vehicles can be regulated to a neighbourhood of its desired value under various working conditions.